Induction and Repression of Hydrolase Genes in Aspergillus oryzae - Tanaka, Mizuki; Gomi, Katsuya (Frontiers in Microbiology, 2021)
The filamentous fungus Aspergillus oryzae, also known as yellow koji mold, produces high levels of hydrolases such as amylolytic and proteolytic enzymes. This property of producing large amounts of hydrolases is one of the reasons why A. oryzae has been used in the production of traditional Japanese fermented foods and beverages. A wide variety of hydrolases produced by A. oryzae has been used in the food industry. The expression of hydrolase genes is induced by the presence of certain substrates, and various transcription factors that regulate such expression have been identified. In contrast, in the presence of glucose, the expression of the glycosyl hydrolase gene is generally repressed by carbon catabolite repression, which is mediated by the transcription factor CreA and ubiquitination/deubiquitination factors. In this review, we present the current knowledge on the regulation of hydrolase gene expression, including carbon catabolite repression, in A. oryzae.